Pengaruh Penggunaan Model Pembelajaran Group Investigation Berbantuan Media Video Powtoon Terhadap Minat dan Hasil Belajar Peserta Didik - Elisa Dianawati; Ria Herdhiana; Cucu Lisnawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Langlangbuana, 2018)
This study aims to (1) knowing the differences in the interest of students in the experimental class using the investigation group learning model assisted by powtoon video media with the control class using the CPTT method (2) knowing the differences in learning outcomes of students in the experimentalclassusingthe investigation group learning model assisted by powtoon video media with the control class using the CPTT method (3) knowing the positive relationship between interest with the learning outcomes in the experimental class using the group investigation learning model assisted by powtoon video media.This type of research is an experimental study with noequivalent pretest posstest controlgroupdesign.The study population was X AP class 3 Bandung Vocational High School with a sample of class X AP 4 andXAP5. The instruments used in the study were interest questionnaires and learning outcome tests. Theresults showed that there were differences between students 'interests and learning outcomes after thetreatment,the learning outcomes of students in the experimentalclass using different group investigation models with the control class using the CPTT method, and there wasa positive relationship between interest in students' learning outcomes.